N-nitrosamines in the southern Swedish rubber industries – exposure, health effects, and immunologic markers - Jönsson, Lena S.; Lindh, Christian H.; Bergendorf, Ulf; Axmon, Anna; Littorin, Margareta; Jönsson, Bo AG (Scandinavian Journal of Work, Environment & Health, 2009)
' ' OBJECTIVES ': 'The aim of this study was twofold: (i) to evaluate the air levels of N-nitrosamines in the Swedish rubber industry and (ii) to estimate the risk of symptoms and changed levels of immunologic markers in relation to these levels. ' ' METHODS ': 'Using adsorption tubes, we collected samples of N-nitrosamines in the breathing zone of 96 rubber workers and analyzed them with liquid chromatography tandem mass spectrometry. Of these 96 workers, 66 were included in a medical examination and blood analysis together with an additional 106 rubber workers and 118 unexposed subjects. Medical and occupational histories were obtained in structured interviews, symptoms were recorded and immunologic markers analyzed in blood. ' ' RESULTS ': 'The sum of N-nitrosamines ranged from less than the limit of detection to 36 µg/m3 and differed with the vulcanization (ie, curing process) method used. Workers vulcanizing with a salt bath had the highest levels (median 4.2 µg/m3). Compared to the unexposed subjects, the rubber workers had an increased risk of nosebleeds, eye and throat symptoms, hoarseness, cough, nausea, headache, and changed levels of eosinophils and total immunoglobulin G (IgG). However, we found no clear exposure-response relationship with the symptoms or the immunologic markers studied. ' ' CONCLUSIONS ': 'High levels of N-nitrosamines were found and must be lowered considerably in order to decrease the risk of cancer. There is a need for an occupational exposure limit for N-nitrosamines in Sweden. The lack of exposure-response relationships with the subacute symptoms examined in this study may be due to a healthy-worker selection or to the possibility that the symptoms are caused by an exposure not co-varying with N-nitrosamines.
Keywords: airway symptom; antibody; biomarker; exposure; exposure-response relationship; health effect; immunologic marker; N-nitrosamine; rubber industry; Sweden